2009
DOI: 10.1111/j.1567-1364.2008.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

The ABC transporter-encoding geneAFR1affects the resistance ofCryptococcus neoformansto microglia-mediated antifungal activity by delaying phagosomal maturation

Abstract: The pathogenic yeast Cryptococcus neoformans has evolved several strategies to survive within phagocytes. Recently, it has been demonstrated that upregulation of the ATP binding cassette transporter-encoding gene antifungal resistance 1 (AFR1) is important not only for determining the resistance of C. neoformans to fluconazole but also in influencing fungal virulence. In the present study, we showed that the fluconazole-resistant AFR1-overexpressing mutant strain was not sensitive to microglia-mediated anticry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…For example, the Cryptococcus neoformans ABC transporter AFR1 was shown to interfere with lysosome acidification in macrophages to increase its survival. In particular, azole-resistant isolates showing increased AFR1 expression were more virulent than their parental azole-susceptible isolates [35], [36], [37], which highlights the relevance of the association between drug resistance and virulence observed here. Interestingly, a recent study reported that AFR1 upregulation could be obtained by reversible chromosome duplication and thus suggests C. neoformans could use this mechanism to modulate its virulence [38].…”
Section: Discussionsupporting
confidence: 59%
“…For example, the Cryptococcus neoformans ABC transporter AFR1 was shown to interfere with lysosome acidification in macrophages to increase its survival. In particular, azole-resistant isolates showing increased AFR1 expression were more virulent than their parental azole-susceptible isolates [35], [36], [37], which highlights the relevance of the association between drug resistance and virulence observed here. Interestingly, a recent study reported that AFR1 upregulation could be obtained by reversible chromosome duplication and thus suggests C. neoformans could use this mechanism to modulate its virulence [38].…”
Section: Discussionsupporting
confidence: 59%
“…ABC transporters in Cryptococcus neoformans are implicated in azole transport, as shown for CnMDR1 by heterologous expression in S. cerevisiae or as in the case of CnAFR1 in C. neoformans directly. Furthermore, interaction studies with a CnAFR1-overexpressing strain and microglia (macrophages residing in the brain) showed reduced acidification and delayed maturation of the phagolysosome [34]. This leads to an interesting connection between azole resistance and virulence, which has also been observed for C. glabrata azole-resistant strains [35].…”
Section: Inventory Of Abc Proteins In Candida Species and Other Pathomentioning
confidence: 76%
“…A lack of cryptococcal killing by human alveolar macrophages in a previous study was hypothesized to be due to a lack of phagosome–lysosome fusion (Vecchiarelli et al ., ). A similar lack of acidification has been seen in microglia cells (specialized phagocytes of the central nervous system), in which only 35% of phagosomes underwent full acidification (Orsi et al ., ).…”
Section: Discussionmentioning
confidence: 97%